Trader of secrets [compact disc, unabridged] - Martini, Steve, 1946- (Martini, Steve, 1946- Paul Madriani novel, 2011)
"Defense attorney Paul Madriani is on the trail of two NASA scientists who are harboring secrets that a dangerous government will stop at nothing to get. Meanwhile, Madriani's daughter, Sarah, is kept under armed guard after eluding the dangerous killer known as Liquida. However, Sarah slips past her protectors, ignorant to the fact that Liquida is waiting for her. Now Madriani, Joselyn Cole, and Harry Hinds must locate the scientist and track down Liquida before all is lost"--Container.